Respuesta :

Answer:

x = 3y + 1

Step-by-step explanation:

You need to find the relationship between x and y before finding the y-intercept.

0-(-1) = 1

1-0 = 1

2-1 = 1

1-(-2) = 3

4-1 = 3

7-4 = 3

As x increases by 1, y increases by 3.

At x = 0, y is already 1. Thus:

x = 3y + 1

Answer:

Slope-intercept For: [tex]y = 3x + 1[/tex]

Standard Form: [tex]9x - 3y = -3[/tex]

Point-slope Form: [tex]y - 4 = 3(x - 1)[/tex]

Step-by-step explanation:

Slope-intercept Form: [tex]y = mx + b[/tex]

Standard Form: [tex]Ax + By = C[/tex]

[tex]\frac{y}{-3x} = \frac{3x}{-3x} + 1\\-3(-3x + y = 1)\\9x -3y = -3[/tex]

Point-slope Form: [tex]y_2 - y_1 = m (x - x_1)[/tex]

[tex](1, 4)\\y - 4 = 3 (x - 1)[/tex]

ACCESS MORE